Thermoliquefaction of palm oil fiber (Elaeis sp.) using supercritical ethanol. (April 2017) - Oliveira, Aline L.P.C.; Almeida, Priscila S.; Campos, Maria C.V.; Franceschi, Elton; Dariva, Cláudio; Borges, Gustavo R.
Highlights: Thermoliquefaction of palm oil fiber was studied employing supercritical ethanol. The proposed apparatus dispenses the use of biomass slurries. Bio-oil yields ranged from 56% to 84% depending on the experimental conditions. Abstract: Thermoliquefaction of palm oil fiber was investigated using supercritical ethanol as solvent. A semi-continuous laboratory scale unit was developed to investigate the effects of temperature (300–500 °C), heating rate (10–30 °C.min −1 ) and cracking time (10–30 min) on the conversion of biomass in bio-oil. The main advantage of the proposed process is that a pure solvent is pumping through the reactor that contains the biomass, dispensing the use of biomass slurries. The yield of bio-oil ranged from 56% to 84%, depending on the experimental conditions. It was observed that an increase in working temperature led to an increase in the bio-oil production. Cracking time and heating rate variation had not shown a considerable effect on the conversion of biomass. The chemical profiles of bio-oil determined by GC/MS, indicate that at low temperature mainly sugar derivatives are produced, while at higher temperatures alcohols and phenolic are the majority compounds of the bio-oil.